Protein content of antivenoms and relationship with their immunochemical reactivity and neutralization assays - de Roodt, Adolfo R. (2014)
Fil: de Roodt, Adolfo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.